Nombrar la muerte: la labor de los funcionarios forenses y acompañantes psicológicos durante la restitución de cuerpos en el proceso de búsqueda humanitaria en Ayacucho en 2023 - Jarufe Caballero, Mauricio (2025)
Under a qualitative-ethnographic methodology, this paper reports the findings obtained during fieldwork practice held in May, 2023 in Ayacucho Perú, as part of the Anthropology program at the Pontificia Universidad Católica del Perú. This paper describes the work of forensic officials and psychological companions during the restitution of human remains of victims from the Internal Armed Conflict in Perú, as well as the relations established with the families of the disappeared. This paper includes ethnographic data gathered from participant observation during the anatomical assemblage of the remains and the official ceremony of restitution, as well as data from semi-structured interviews with State officials, NGO associates and relatives of the returned disappeared persons.We frame the restitution process as a series of actively politicized events that display State-imposed narratives of closure and reparation, further affecting the mourning of the victims and their relation with the State. We analyze the symbolic dimension of the anatomical assemblage, describing the embodiment of the disappeared being, the multiple ontologies of human remains and the different forms of mourning that arise from them. Due to the conditions previously described, we conclude that forensic officials and psychological companions adopt different strategies to legitimize their work in the interactions with the families of the disappeared, and the way their own perspectives on death and restitution affect these relations.